Hybrid Identity Students in Modern Learning: Educational Management Perspectives on Digital Academic Identity - Risza Presty Rumani (Pt. Anagata Sembagi Education, 2025)
This study investigates the phenomenon of Hybrid Identity Students (HIS) within the context of modern learning increasingly dominated by digital platforms. The evolving digital academic identity among students creates new challenges for educational management in designing effective, inclusive, and sustainable learning environments. Through a systematic literature review approach analyzing 20 internationally reputed journal articles (2021–2024), this study aims to identify HIS characteristics, technology adoption patterns in learning, and managerial implications for higher education institutions. Results indicate that HIS develop two interacting identity layers: physical-traditional identity and digital-academic identity. Key findings include: (1) 72% of students experience identity conflict when transitioning between learning modalities; (2) adaptive AI integration increases student engagement by up to 65%; and (3) digital competence positively correlates with academic performance (r = 0.74). This study contributes to developing a conceptual framework for digital academic identity management in hybrid learning systems.